Unique Health System - 2010: room for a turning point - Rodrigues dos Santos, Nelson (O Mundo da Saúde, 2010)
This study emphasizes landmark advances in the implementation of SUS constitutional principles and guidelines, especially universality and decentralization, which allowed for the greatest ever social inclusion process in the public system of health. We also emphasize advances in public system management with the implementation of Health Funds, of fund individual financing and joint management commissions (tripartite and bipartite), of agreed basic operational norms and recently, the Pact for Life in Defense of SUS and Management, which now reaches the “post-BOG” [Basic Organizing Guidelines] stage. We also identify limits to these advances, configured by rigid obstacles to the advance of public and contracted management of the health network and each unit of public services, still under the predominant logic of interests linked to the old management model characterized by a historical mixture of public subfinancing, the interruption of State reform/a nebulous State-private organizations relationship. Such limits, more than obstacles to the continuity of the advances, has excluded equity, integrality, regionalization, the work of health councils in strategy elaboration, and demarcating the implementation of the route to “Poor SUS for the poor and complementary SUS to health management organizations’ affiliates”. We also discuss potential and embryonic possibilities for a “turning point” in public health policies, aiming at retrieving values paved in the human right to health, the social conscience of health necessities and the correspondent rights, with a real adhesion of the middle class, of unions and public workers and with a effectively democratic civil society-State relationship.